STRUCTURE OF COGNITIVE DISORDERS AND DYNAMICS OF BIOELECTRIC ACTIVITY OF THE BRAIN IN PATIENTS AFTER DIRECT MYOCARDIAL REVASCULARIZATION - O. A. Trubnikova; I. V. Tarasova; A. S. Mamontova; I. D. Syrova; O. V. Maleva; O. L. Barbarash (Российский кардиологический журнал, 2014)
Aim. To analyze structural chareacteristics and electroencephalographic (EEG) pattern of post-operation cognitive dysfunction (POCD) in patients after direct myocardial revascularization under artificial circulation (AI). Material and methods. Totally 114 male-patients included, underwent scheduled coronary bypass grafting (CBG) under the AI, with average age 55,9±5,3 y. In 3-5 days before operation and on 7-10 day after all patients underwent neurophysiological testing; of those 65 patients also underwent EEG. Results. The CBG operation with AI leads in 79% of cases to the early POCD. Cognitive impairment usually becomes prominent in the domains of neurodynamics and memory. It is shown that the early POCD is followed by EEG-signs of cortical dysfunction (increase of low-frequency theta-rhythm magnitude).Conclusion. According to the results of the study, in post-operative CBG with AI period the structure of POCD consists of injury of neurodynamics and memory, which might be a cause of decreased life quality of patients and efficacy of surgery itself.